Poéticas do deslocamento : representações de identidades femininas no bildungsroman de autoria feminina contemporâneo - Coqueiro, Wilma dos Santos (2014)
The novel as a great socio-literary institution, which projects the ideals of bourgeois class, becomes the maximum expression of modernity from the 18th century on. The genre, characterized by its malleability and ambivalence, reflects an individualistic and innovative orientation. In this sense, the novels of characters originate subtypes, as the Bildungsroman, whose paradigmatic model would be Wilhelm Meister's Apprenticeship (1795), by the German writer Johann Wolfgang von Goethe. Since the novel is a genre in constant becoming, the concept of Bildungsroman undergoes problematizations and revisions and, today, it is possible to consider a novel of formation which includes ethnic, racial and sexual minorities. Some important steps in male Bildungsroman, such as fulfillment in love from several experiences and the discovery of a professional vocation and a philosophy of life, are still problematic in female novels of formation along the 20th century, due to the small space dedicated to woman in society, making her formative experiences more subjective, and culminating, in most cases, in the failed end of characters who cannot escape the webs of social oppresion. To the question that underlies this research - if the female novel of formation can innovate in the 21th century, presenting trajectories of women subjects - corresponds the hypothesis that in the analyzed novels there is a process of subjectification of the female characters, in which the formative experiences occur through spatial and identity displacements, characteristic of modern times. If along the 20th century the heroines have still felt the weight of patriarchal tradition, not infrequently having to forgo social integration on behalf of individualization and self-realization, as the characters Conceição from O Quinze and Joana from Perto do coração selvagem, in the novels of formation from the 21th century - such as Pérolas Absolutas (2003), by Heloísa Seixas, Algum Lugar (2009), by Paloma Vidal, and Azul-corvo (2010), by Adriana Lisboa, - amid globalization and the dismantling of great utopias and truths, they experience other conflicts and problems resulting from the fluidity of human relations in modern times. Since this work is inserted in the line of research "Literature and building of identities", the reading and analysis of the chosen corpus is based mainly on theoretical contributions from Cultural Studies and Feminist Criticism. With this thesis, we hope to contribute to the studies of contemporary feminist criticism, showing that the characters in the post-modern scene, in their search for subjectification, undergo experiences of displacement and disintegration of identities, but seek, despite setbacks, a building of themselves as women.